Unburdening expectation and operating between: architecture in support of palliative care. Issue 4 (16th March 2022) - Mclaughlan, Rebecca; George, Beth
Abstract : The role of design and materials in the enactment and experience of healthcare has gained increasing attention across the fields of evidence-based design, architecture, anthropology, sociology and cultural geography. Evidence-based design, specifically, seeks to understand the ways in which the built environment can support the healing process. In the context of palliative care, however, the very measure of healing differs vastly. Physicians Mount and Kearney suggest that 'it is possible to die healed', and that such healing can be facilitated through the provision of 'a secure environment grounded in a sense of connectedness' (2003: 657). Acknowledging this critical difference raises important questions around the various ways through which the built environment might support healing, but also about the potential of architecture to impart care. This paper reports on 15 interviews with architects, experienced in the design of palliative care settings, from the UK, USA and Australia, to provide a deeper understanding of the questions being asked within the briefing processes for these facilities, the intentions embedded in the ways that architects respond, and the kinds of compromises deemed allowable (by various stakeholders) within the procurement process. Our findings suggest that palliative care architects often respond to two briefs, one explicit and the other unspoken. Design responses in relation to the first include: formally expressing a differentiation in the philosophy of care (signalling difference), attention to quality, extending comfort and providing 'moments'. The second relates to the unburdening of palliative care facilities from their associative baggage and responding to the tension between the physical and imaginative inhabitation of space. In revealing the presence of this hidden brief, and the relationship between the two, this paper invites a broader discussion regarding the capacity of architecture to support palliative care patients, their families and staff.